Life-purpose orientations of patients with coronary artery disease - E. A. Zakharyan; I. V. Zyabkina (Кардиоваскулярная терапия и профилактика)
Aim. To study the role of life-purpose orientations in patients with coronary artery disease (CAD) in the context of their clinical characteristics.Material and methods. The study included 286 people, including 242 patients with an established diagnosis of CAD and 44 healthy volunteers (control group). Patients underwent coronary angiography and echocardiography. In order to determine the axiological and conative orientations of the individual, the Life-Purpose Orientations questionnaire by D. A. Leontiev was used.Results. No differences in life meaningfulness level were found between CAD patients and healthy respondents (p>0,05). The patients admitted for elective cardiac surgery had lower life-purpose indicators compared to the patients hospitalized for conservative therapy (p<0,05). Lower values were found for the overall life meaningfulness, "goals in life" and "life process" scales in patients with permanent atrial fibrillation (p<0,05), as well as for the "locus of self-control" and "locus of life control" scales in patients with paroxysmal atrial fibrillation (p<0,05) compared to patients with sinus rhythm. In patients with chronic left ventricular aneurysm, lower life meaningfulness values were also noted (p<0,05) than in individuals without it. An inverse correlation was obtained between the age of the subjects and most questionnaire indicators of life-purpose orientations (p<0,05).Conclusion. Analysis of the obtained data showed the significance of the subjective experience of disease symptoms for patients with CAD.